Study of histopathological spectrum of non-neoplastic lesions of the lung in autopsy specimen - Guru, Aayushi; Meena, Hariom; Sanjuna Dharmalingam; Singh, Nikita; Suresh Kumar Sutrakar (Asian Journal of Medical Sciences, 2022)
Background: Lungs are the major organ involved in infectious and occupational diseases almost secondarily involved in all forms of terminal diseases. Autopsy plays an important role in identifying and understanding the pathology of various respiratory diseases and lung lesions to find out the parenchymal pathology. Aims and Objectives: This study aims to study the histopathological spectrum of non-neoplastic lung lesions in medicolegal autopsy and to assess the frequency of spectrum of lung lesions. Materials and Methods: The present retrospective study was carried out in the Department of Pathology, Shyam Shah Medical College, Rewa, M.P., for a period of 18 months from July 2020 to January 2022. All 98 consecutive specimens of medicolegal autopsy were included with age from newborn to 70 years irrespective of gender and cause of death. The results were analyzed based on gross and microscopic findings. Results: Among the 98 cases studied, 82 cases (84%) were of diseased and 16 cases (16%) were of non-diseased lung. The most common age group affected was 30–39 years with 30% of affected cases followed by 20–29 years with 21% of affected cases. Among 82 cases, the most common pulmonary lesion was pneumonia in 46% (45/98) of the total cases followed by congestion and edema seen in 22% (21/98) of the cases. Conclusion: Histopathological study of lung autopsy helps in providing information for clinical diagnosis of non-neoplastic lung lesions that act as a tool for better clinical assessment and help to establish a correct prophylactic measure. The histopathological examination (HPE) helps in establishing the final cause of death. The HPE helps in establishing the final cause of death. Therefore, autopsy study is very helpful in refining the vision and diagnostic setup for better evaluation.